Genetic Discrimination in Access to Life Insurance: Does Ukrainian Legislation Offer Sufficient Protection against the Adverse Consequences of the Genetic Revolution to Insurance Applicants? - Arych, Mykhailo; Joly, Yan (My University, 2022)
This paper presents an inter-disciplinary study of the risk for, and protections against, genetic discrimination in access to life insurance in Ukraine. It aims (i) to review questions related to genetic information, health status, and family history currently included in Ukrainian life insurance application forms; (ii) to analyze the Ukrainian legislation related to equity and nondiscrimination and to determine whether it provides adequate protection against genetic discrimination (GD). Research findings of our insurance application forms review show that Ukrainian life insurance companies ask broad questions about health and family history that may be perceived by applicants as requiring the disclosure of their genetic information. Our legal analysis shows that today there are no genetic specific law protecting Ukrainians people against GD in insurance. However, Ukrainian human rights legislation provides some protection against multiple grounds of discrimination and given the ratification by Ukraine of the European Convention on Human Rights it is possible that these grounds could be interpreted by tribunals as also including genetic characteristics.
Keywords: genetic discrimination; genetic information; life insurance; legislation; human rights; Ukraine; Europe; генетична дискримінація; генетична інформація; страхування життя; законодавство; права людини; Україна; Європа; кафедра фінансів